S129 Inflammatory Cytokines Influence Respiratory Epithelial Anti-viral Immune Responses Via Inducible Epigenetic Control Of Rig1 Expression: A Model Of Early Life Origins Of Asthma?. (10th November 2014) - Spalluto, CM; Singhania, A; Woelk, CH; Sanchez-Elsner, T; Staples, KJ; Wilkinson, TMA
Abstract : The development of asthma is linked to early life environmental exposures and the occurrence of severe viral infections. Rapid maturation of adaptive immunity from a tolerant (Th2) to an anti-infective (Th1) state occurs in the neonatal period. We hypothesised that the airway inflammatory milieu, driven by the maturing immune response to environmental exposures may have important effects on the development of anti-viral innate immunity at the level of the epithelium. We studied whether the inflammatory environment of the airway epithelium modulates gene expression via epigenetic regulation of anti-viral genes as a model of the development of a long term abnormality which is a hallmark of asthma. We optimised an in-vitro model using AALEB, human immortalised bronchial epithelial-derived cells which were pre-treated for 24 h with cytokines that mimic Th1 environment (IFNy, 10 ng/ml) and Th2 (IL-13, 10 ng/ml) before being infected with RSV A, MOI=2 for 48 h. Quantitative real-time PCR with Taqman primers was used to assess expression of innate genes. Cells were collected after 48 h and stored in Trizol. Chromatin Immuno Precipitation (ChIP) with antibodies against histone modifications was used to assess epigenetic controls. In order to confirm epigenetic regulation of innate genes we used a panel of HAT, HDAC and histone demethylase inhibitors. We initially studied the impact of cytokines on a range of innate anti-viral genes. RIG1 was differentially expressed and reductions in expression associated with higher viral titres. IFNy priming induced increases in RIG1 mRNA at 48 h that correlated at the promoter with enrichment of H3K9ac and RNApolII (active-promoters) and reduction of H3K9me3 (repressive-promoters). We observed a statistically significant increase of RIG1 expression by IFNγ when co-incubated with SAHA (HDAC I and II inhibitors) and JIB-04 (Pan-Jumanji histone demethylase inhibitor). No effects of Th2 priming were seen at the level of antiviral responses. This in-vitro study suggests the inflammatory environment of naive epithelial cells can induce epigenetic modulation of innate immune responses at the level of histone methylation and acetylation and hence potentially lead to long term impacts on anti-viral immunity. The presence of a Th1 milieu appears key to the development of effective anti-viral responses.